Comprehensive evaluation of gas production efficiency and reservoir stability of horizontal well with different depressurization methods in low permeability hydrate reservoir. (15th January 2022) - Yin, Faling; Gao, Yonghai; Zhang, Heen; Sun, Baojiang; Chen, Ye; Gao, Dongzhi; Zhao, Xinxin
Abstract: Two successful trials in South China Sea show that low-permeability hydrate reservoirs have broad exploitation prospects. Currently, gas production efficiency and reservoir stability are key factors restricting the commercial exploitation. For improving development efficiency and evaluating reservoir stability, it is necessary to comprehensively evaluate different depressurization schemes. Based on the drilling data of hydrate reservoirs in South China Sea, a thermal-fluid-solid-chemical multi-field coupling model was established to analyze temporal and spatial evolution characteristics with three depressurization modes: regular depressurization(RD), step-wise depressurization(SD) and cycling depressurization(CD). The results show that compared with RD, SD and CD can improve production capacity in different degrees. Due to the limitation of convective heat transfer in low-permeability reservoir, RD productivity is mainly affected by formation sensible heat. SD and CD are mainly affected by formation sensible heat in early stage and formation latent heat plays a role in later stage. The formation deformation degree is positively correlated with hydrate decomposition radius. After 180 days, the maximum subsidence at reservoir and mudline is 0.0609 m and 0.0135 m respectively. Production and subsidence ratio(PSR) is proposed to evaluate different depressurization schemes. Finally, CD2 is the best scheme for low-permeability hydrate reservoir and PSR value is 20298.3 m 3 /cm. Highlights: Coupling response of multiple physical fields in low permeability hydrate reservoir. Comprehensively evaluate the productivity and reservoir stability of different schemes. SD and CD can alleviate the rapid geothermal loss of reservoir in varying degrees. Formation deformation is positively correlated with hydrate decomposition radius.